In vitro evaluation of the anti-pathogenic activity of Okoubaka aubrevillei on the human gastrointestinal tract - Buchheim-Schmidt, Susann; Peters, Uwe; Duysburgh, Cindy; Van den Abbeele, Pieter; Marzorati, Massimo; Keller, Thomas; Martin, David; Klement, Petra; Baumgartner, Stephan (Zeitschrift für Gastroenterologie, 2021)
Background Okoubaka aubrevillei is used in traditional West African medicine and in homeopathy for treatment and prevention of several gastrointestinal problems. The aim of this in vitro study was to evaluate the effect of repeated doses of two Okoubaka products (10 % ethanolic tincture, mother tincture (MT); 3rd decimal potency, 3X) on the microbial activity of physiological human colon microbiota using a Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) and to investigate any preventive effect against infections with diarrhea-causing pathogens.Methods Upon inoculation with fecal microbiota from a healthy donor, 4 parallel proximal colon compartments of the SHIME were treated either with Okoubaka MT, Okoubaka 3X, ethanol control or blank control for 7 days. Using the Okoubaka-adapted microbial community from SHIME, 48 h challenge tests were performed with enterotoxigenic Escherichia coli (ETEC) and Salmonella enteritidis in 4 different doses (103–108 colony forming units as typical in vivo infectious doses). Pathogen concentrations, short-chain fatty acids (SCFAs) and branched SCFA production were measured in triplicate at 0, 24 and 48 h.Results In the challenge tests, both Okoubaka products were able to restrict the colonization of ETEC and Salmonella at 3 of the 4 pathogen doses (except the highest doses), with a stronger anti-pathogenic effect for MT, which included a reduction of 2.0 log-units of ETEC (p < 0.0001) and 1.1 log-units of Salmonella (p < 0.0001). Total SCFA levels remained unaffected, but butyrate increased during the first 24 h (p < 0.0001 for ETEC), accompanied by decreased acetate production.Conclusion We observed in vitro a systemic activating effect of Okoubaka on intestinal microbiome resistance, which resulted in an anti-pathogenic effect, especially against ETEC. We hypothesize that the mode of action in vivo is also based on systemic regulative effects.
Keywords: Okoubaka; microbiome; traveler’s diarrhea; gastroenterititis; ETEC; Simulator of the Human Intestinal Microbial Ecosystem (SHIME®); SCFA; butyrate